Association of serum uric acid level with non-alcoholic fatty liver disease: A cross-sectional study - Li, Youming; Xu, Chengfu; Yu, Chaohui; Xu, Lei; Miao, Min (Journal of hepatology, 2009)
Serum uric acid level has been suggested to be associated with factors that contribute to the metabolic syndrome. The aim of this study was to investigate the association of serum uric acid level with non-alcoholic fatty liver disease (NAFLD). A cross-sectional study was performed among the employees of Zhenhai Refining & Chemical Company Ltd., Ningbo, China. The study included 8925 subjects (6008 men) with a mean age of 43 years. The prevalence rates of NAFLD and hyperuricemia were 11.78% and 14.71%, respectively. NAFLD patients had significantly higher serum uric acid levels than controls (370.3±86.6 vs. 321.1±82.6μmol/L; P<0.001). The prevalence rate of NAFLD was significantly higher in subjects with hyperuricemia than in those without hyperuricemia (24.75% vs. 9.54%; P<0.001), and the prevalence rate increased with progressively higher serum uric acid levels (P value for trend <0.001). Multiple regression analysis showed that hyperuricemia was associated with an increased risk of NAFLD (odds ratio [OR]: 1.291, 95% confidence interval [CI]: 1.067–1.564; P<0.001). Serum uric acid level is significantly associated with NAFLD, and elevated serum uric acid level is an independent risk factor for NAFLD.